Makeup in pharmacies: how can Vichy Portugal grow its makeup category in pharmacies - Sesinando, Maria José Ribeiro (2020)
The makeup market in Portugal is considerably smallerthan inother countries. However, its significant growth led Vichy, a dermo-cosmetic brand, toinvest in it. Being the brand sold in pharmacies and drugstores–an underdeveloped makeup channel in Portugal–achallenge arose: “How can Vichy grow its makeup category in pharmacies?”. This issuewas addressed withprimary and secondary research, which concluded,amongst other findings,that consumersonly buy pharmacy makeupfor skin problems. Therefore, several recommendations to grow Vichy’s makeup were made, including a new positioning; packagingadjustments;solutions for pharmacies and a campaign forVichy’smakeup rebranding.